2022
DOI: 10.1108/ijsi-03-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of waste glass powder, microsilica and polypropylene fibers on ductility, flexural and impact strengths of lightweight concrete

Abstract: PurposeToday, using lightweight structural concrete plays a major role in reducing the damage to concrete structures. On the other hand, lightweight concretes have lower compressive and flexural strengths with lower impact resistance compared to ordinary concretes. The aim of this study is to investigate the effect of simultaneous use of waste glass powder, microsilica and polypropylene fibers to make sustainable lightweight concrete that has high compressive and flexural strengths, ductility and impact resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 73 publications
(118 reference statements)
0
14
0
Order By: Relevance
“…In their review, Khan et al [42] dealt with shrinkage, absorption, ASR expansion, sulfate and chloride attack, and mechanical characteristics of cementitious materials that contained waste glass. Past research [43][44][45][46] has shown that using waste glass powder, micro-silica and fibers can improve the behavior of concrete. Mohajerani et al [47] extended their review by considering the practical use of waste glass in subbase and base of roads, asphalt concrete, and ultra-weight concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Khan et al [42] dealt with shrinkage, absorption, ASR expansion, sulfate and chloride attack, and mechanical characteristics of cementitious materials that contained waste glass. Past research [43][44][45][46] has shown that using waste glass powder, micro-silica and fibers can improve the behavior of concrete. Mohajerani et al [47] extended their review by considering the practical use of waste glass in subbase and base of roads, asphalt concrete, and ultra-weight concrete.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have done a lot of research on the effect of different types of fibers on the different properties of concrete, including its mechanical properties, and all the evidence indicates that the use of fibers alone or in a hybrid form can improve the mechanical behavior of fibers. Also, the use of environmentally friendly additives along with fibers, besides being sustainable, can help make high‐performance concrete 40–49 …”
Section: Introductionmentioning
confidence: 99%
“…(2020). The best performance in terms of mechanical and impact characteristics was found out on using 25% GW powder and 10% microsilica powder (Najaf et al. , 2022a, b).…”
Section: Introductionmentioning
confidence: 99%